Erdheim-Chester Disease and Small Lymphocytic Lymphoma Collision Tumour Presenting as a Perirenal Mass - Antonio Maietta; Maryam Razmpoosh (Case Reports in Pathology)
Background. Erdheim-Chester disease is a rare histiocytic neoplasm associated with MAPK pathway mutations. Disease manifestation is variable often involving many different organs, mainly bone, retroperitoneum, the heart, and the central nervous system. Histological findings include foamy histiocytes in a fibrous stroma with scattered inflammatory infiltrate. Histiocytes are CD68 positive and S100 negative. Case Report. We report a case of Erdheim-Chester disease associated with small lymphocytic lymphoma presenting as a perirenal mass with a review of the recent literature. Conclusions. Erdheim-Chester disease rarely can be associated with other cancers, namely myeloid neoplasms. We report a case of Erdheim-Chester disease presenting with small lymphocytic lymphoma as a perirenal mass. The association of Erdheim-Chester disease with lymphoproliferative disorders needs to be elucidated.